2017
DOI: 10.3892/br.2017.889
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the function of microRNA-375 in humans using bioinformatics

Abstract: Abstract. ) is expressed at low levels in many types of solid tumor, particularly in gastrointestinal tumors. It is considered to be important in the development of cancer and certain diseases. Thus, more detailed knowledge is required on the particular functions of miR-375. miRs function by regulating target genes. Therefore, in the current study, miRWalk (which includes the data from 10 prediction software programs) was used to predict the target genes of miR-375. The genes, which were co-predicted using fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Several miRs with altered expression in catecholamine-producing pheochromocytomas and paragangliomas (such as miR-15, -16, -21-3p, -96, -101-, -133, -137, -139-3p, -183, -195, -210, -338-3p, -375, -382, -483-5p, -488, -508, -765, -855, and -1225-3p) were reported [ 35 ]. In particular, there are a few reports on the function of miR-375, and they suggested it to be involved in the regulation of cytokines, extracellular matrix–receptor interaction, focal adhesion, phosphatidylinositol-3 kinase-protein kinase B (Akt), amoebiasis, and protein-processing pathways [ 36 ]. Single nucleotide polymorphisms (rs11174811 and rs3803107) in miR-375 target sites of the 3′-untranslated region in the arginine vasopressin receptor 1a gene were reported to be associated with the risk of hypertension [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several miRs with altered expression in catecholamine-producing pheochromocytomas and paragangliomas (such as miR-15, -16, -21-3p, -96, -101-, -133, -137, -139-3p, -183, -195, -210, -338-3p, -375, -382, -483-5p, -488, -508, -765, -855, and -1225-3p) were reported [ 35 ]. In particular, there are a few reports on the function of miR-375, and they suggested it to be involved in the regulation of cytokines, extracellular matrix–receptor interaction, focal adhesion, phosphatidylinositol-3 kinase-protein kinase B (Akt), amoebiasis, and protein-processing pathways [ 36 ]. Single nucleotide polymorphisms (rs11174811 and rs3803107) in miR-375 target sites of the 3′-untranslated region in the arginine vasopressin receptor 1a gene were reported to be associated with the risk of hypertension [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…44,48,51,54,[56][57][58][59] In NSCLC, miRNA-375 is associated with poor prognosis. 43,44,60 Interestingly, miRNA-375 is strongly associated with the Wnt/ b-catenine pathway 49 and the Hippo pathway, 59,[61][62][63] known to be involved in ICIs resistance. [64][65][66][67][68][69][70] Moreover, miRNA-375 targets the JAK2 gene, 62,71 involved in the IFN-g and TNF-a pathways, key-regulators of cytotoxic CD8C immune response.…”
Section: Discussionmentioning
confidence: 99%
“…43,44,60 Interestingly, miRNA-375 is strongly associated with the Wnt/ b-catenine pathway 49 and the Hippo pathway, 59,[61][62][63] known to be involved in ICIs resistance. [64][65][66][67][68][69][70] Moreover, miRNA-375 targets the JAK2 gene, 62,71 involved in the IFN-g and TNF-a pathways, key-regulators of cytotoxic CD8C immune response. 72 Taken together, these data, highlighted by our results, suggest an implication of both miRNA-320b and miRNA-375 in anti-tumour immune response with ICIs, and the potential utility of screening for these miRNA in plasma before beginning nivolumab to select patients who will have response and clinical benefit with this treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in a clinical study, Andersen and colleagues [25] described an increased expression of has-miR-34a-5p in patients with migraine attacks, while Chen et al [26] reported that hsa-miR-375 plays pivotal roles in cancer, metabolic, immune disease and inflammatory diseases.…”
Section: Introductionmentioning
confidence: 99%